2019
DOI: 10.1097/md.0000000000013795
|View full text |Cite
|
Sign up to set email alerts
|

Hand tendinopathy risk factors in Taiwan

Abstract: De Quervain's disease, carpal tunnel syndrome (CTS), and trigger finger (digit) are three common pathological conditions of the hand. They are considered overuse syndromes and occur predominantly in females. The prevalence rate and cause-specific risks of these three tendinopathies have not yet been clarified. Data from 41,871 cases listed in the Taiwan National Health Insurance Research Database (NHIRD) from 2010 to 2014 were analyzed. The prevalence rate of these 3 conditions by age, sex, and the risk factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 33 publications
0
20
0
3
Order By: Relevance
“…Other diagnoses of tennis and golfer's elbow, carpal tunnel syndrome and trigger finger were less prevalent but were still much more common when compared to the non-playing limb. The incidence of these disorders was also higher in comparison to the average population 5 , 7 - 9 .…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Other diagnoses of tennis and golfer's elbow, carpal tunnel syndrome and trigger finger were less prevalent but were still much more common when compared to the non-playing limb. The incidence of these disorders was also higher in comparison to the average population 5 , 7 - 9 .…”
Section: Discussionmentioning
confidence: 79%
“…Those complaining of wrist symptoms were found to have de Quervain’s tenosynovitis 80% of the time, which was the commonest diagnosis on clinical examination, with an incidence of 54%. This incidence is considerably higher than in the average population; only 0.49% of the population were reportedly affected by de Quervain’s tenosynovitis in one recent study 5 , and even so, it was more routinely found in older age groups 5 , 6 . Other diagnoses of tennis and golfer's elbow, carpal tunnel syndrome and trigger finger were less prevalent but were still much more common when compared to the non-playing limb.…”
Section: Discussionmentioning
confidence: 84%
“…In older patients, the prevalence of trigger finger was high for both men and women. 9 Thus, it is uncertain if our finding could be applicable to other populations.…”
Section: Discussionmentioning
confidence: 89%
“…(2019) проведен анализ частоты ПОМТ кисти у 41 871 жителя Тайваня. По данным этого исследования, частота синдрома запястного канала составила 1,59%, синдрома де Кервена -0,49%, щелкающего пальца -1,07% [15]. I. Albers и соавт.…”
Section: îáñóAeäåíèåunclassified